2023
DOI: 10.3389/fevo.2023.1155401
|View full text |Cite
|
Sign up to set email alerts
|

Path analysis of energy economic management standardization in the context of carbon neutralization and carbon peak

Abstract: Carbon neutrality and carbon peak are two important measures to control climate change. They have a huge impact on many companies in the fields of energy, industry, construction, transportation, etc. They can change the development pattern of related industries and increase many new investment and development opportunities. This paper proposes a path analysis of the standardization of energy economic management under the background of carbon neutrality and carbon peak, aiming to study the development forecast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…With the “dual-carbon” target, China’s clean energy industry has seen a period of rapid development. As a vital part of clean energy AC–DC conversion, film capacitors have become commonplace in the sectors of solar power manufacturing, wind power generation, and new energy vehicles. , Film capacitors are also extensively utilized in high-power applications because of their short and efficient power output and long cycle life, including high-power home appliances, LED high light illumination, automotive chargers, and charging heaps for new energy vehicles. Therefore, how to develop film capacitors with high power density is the key to realize energy saving and low-carbon environmental protection . The commonly used dielectric materials for film capacitors mainly include PP, PET, PEN, PPS, and other polymer materials. A film made of biaxially oriented polypropylene (BOPP) obtained by biaxially stretching PP has the advantages of high breakdown strength and low dielectric loss and is a common dielectric material for commercially available film capacitors.…”
Section: Introductionmentioning
confidence: 99%
“…With the “dual-carbon” target, China’s clean energy industry has seen a period of rapid development. As a vital part of clean energy AC–DC conversion, film capacitors have become commonplace in the sectors of solar power manufacturing, wind power generation, and new energy vehicles. , Film capacitors are also extensively utilized in high-power applications because of their short and efficient power output and long cycle life, including high-power home appliances, LED high light illumination, automotive chargers, and charging heaps for new energy vehicles. Therefore, how to develop film capacitors with high power density is the key to realize energy saving and low-carbon environmental protection . The commonly used dielectric materials for film capacitors mainly include PP, PET, PEN, PPS, and other polymer materials. A film made of biaxially oriented polypropylene (BOPP) obtained by biaxially stretching PP has the advantages of high breakdown strength and low dielectric loss and is a common dielectric material for commercially available film capacitors.…”
Section: Introductionmentioning
confidence: 99%
“…Shale gas is a green, low-carbon, clean, unconventional natural gas resource. Its development meets the demand for energy consumption and optimizes the energy consumption structure (He et al, 2022;Li, 2022;Liu, 2023). By utilizing shale gas, carbon emissions can be reduced, effectively mitigating climate warming (Wang, 2022;Cai, 2023;Hu et al, 2023;Liu and Guo, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Li et al (2021a,b) showed that economic growth and economic structure are the most important positive and negative factors affecting carbon emissions. Liu (2023) found that, under the carbon neutral scenario, carbon emissions can be better controlled through carbon neutral and carbon peak strategies.…”
Section: Introductionmentioning
confidence: 99%